Successful treatment of refractory systemic lupus erythematosus-associated immune thrombocytopenia with drug-induced liver injury with telitacicept: a case report and review - Li, Xuefei; Fu, Yao; Yin, HaiQin; Zhu, Huiling (Frontiers in Immunology, 2025)
Immune thrombocytopenia(ITP)is a common clinical manifestation of systemic lupus erythematosus(SLE). Drug therapy includes glucocorticoids(GCs),disease-modifying anti-rheumatic drugs (DMARDs) and biologics. Refractory thrombocytopenia can be life-threatening, and the use of effective medications plays a crucial role in disease improvement. Here, we report a case of ITP secondary to SLE. The use of dexamethasone(DEX), cyclosporine A(CsA), and hetrombopag resulted in drug-induced liver injury. Subsequently, telitacicept was chosen and successfully controlled the patient’s condition. It suggests that telitacicept may be a new treatment option for refractory SLE-ITP.